Discourse studies in cognitive linguistics : selected papers from the Fifth International Cognitive Linguistics Conference, Amsterdam, July 1997 - Van Hoek, Karen; Kibrik, A. A.; Noordman, Leonard G. M., 1940- (Amsterdam studies in theory and history of linguistic science. Current issues in linguistic theory ;, 1999)
This volume presents selected papers from the 5th International Cognitive Linguistics Conference within the area of discourse analysis. The topics addressed include pronominal anaphora in English and Russian narratives, the subtleties of the definite article in English and Spanish, the use of discourse particles in Dutch, and the function of prosody as a marker of text structure in spoken narratives. The papers illustrate the potential of the emerging cognitive linguistic paradigm to provide fresh, revealing insights in the study of discourse.